The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1186/s12913-021-06093-0
|View full text |Cite
|
Sign up to set email alerts
|

Using text analysis software to identify determinants of inappropriate clinical question reporting and diagnostic procedure referrals in Reggio Emilia, Italy

Abstract: Background Inappropriate prescribing of diagnostic procedures leads to overdiagnosis, overtreatment and resource waste in healthcare systems. Effective strategies to measure and to overcome inappropriateness are essential to increasing the value and sustainability of care. We aimed to describe the determinants of inappropriate reporting of the clinical question and of inappropriate imaging and endoscopy referrals through an analysis of general practitioners’ (GP) referral forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Venturelli et al assessed the appropriateness of referrals for imaging and other diagnostic procedures by analysing the requests’ content using a commercial software package. 41 Their study’s focus was on classification results (appropriate vs. not appropriate) and not the applied method’s performance, which impeded comparison with our study. However, the study demonstrated the feasibility of using requests for assessing appropriateness and is an excellent example of a future application for transformer-based NLP.…”
Section: Discussionmentioning
confidence: 95%
“…Venturelli et al assessed the appropriateness of referrals for imaging and other diagnostic procedures by analysing the requests’ content using a commercial software package. 41 Their study’s focus was on classification results (appropriate vs. not appropriate) and not the applied method’s performance, which impeded comparison with our study. However, the study demonstrated the feasibility of using requests for assessing appropriateness and is an excellent example of a future application for transformer-based NLP.…”
Section: Discussionmentioning
confidence: 95%
“…This study supports these concepts. Other studies suggest and explore new techniques, such as text analysis software and other types of automated language processing, in evaluations [ 18 20 ]. This could be a way forward in the future.…”
Section: Discussionmentioning
confidence: 99%
“…While responses may have been influenced by differing interpretations of the question posed as to whether this related to real life practice or to the existence of regulation, it is clear that advance justification is not practically being performed for all CT examinations, given the volume of respondents (47%) who reported that advance justification was performed sometimes or mostly. Although a minority (n = 4) stated that referrals were justified at the point of referral, this could have significant implications for the appropriate use of CT for patients without radiology practitioner oversight, particularly when one considers the poor usage and knowledge of referral guidelines already cited by others [6,8,10,17]. A previous HERCA report [18] following an inspection week in 2016 reported broadly similar findings, with as many as 26% of facilities not performing a satisfactory evaluation of the referral before the examinations were performed and even more not rejecting unjustified examinations (31%) or fully proving that the examinations were authorised by the radiological practitioner (35%).…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate imaging referrals not only reduce the radiation exposure of the population, but importantly also save valuable healthcare resources. However, numerous publications point to a less than ideal level of justification in current practice with national audits reporting up to 39% [5][6][7] of CT examinations not being justified and even higher rates reported across smaller studies [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%